2020
DOI: 10.1002/ange.202000426
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Raman Monitoring and Manipulating of Interfacial Hydrogen Spillover by Precise Fabrication of Au/TiO2/Pt Sandwich Structures

Abstract: The spillover of hydrogen species and its role in tuning the activity and selectivity in catalytic hydrogenation have been investigated in situ using surface‐enhanced Raman spectroscopy (SERS) with 10 nm spatial resolution through the precise fabrication of Au/TiO2/Pt sandwich nanostructures. In situ SERS study reveals that hydrogen species can efficiently spillover at Pt‐TiO2‐Au interfaces, and the ultimate spillover distance on TiO2 is about 50 nm. Combining kinetic isotope experiments and density functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Quantification of the H 2 -TPR curves (Supplementary Table 1 ) shows that the hydrogen consumed by NiO/Al 2 O 3 /Pt (1.86 mmol H 2 g –1 ) is greater than the sum of the hydrogen consumed by Al 2 O 3 /Pt (0.31 mmol H 2 g –1 ) and NiO/Al 2 O 3 (1.29 mmol H 2 g –1 ). These results demonstrate that the reduction of NiO species is promoted after Pt addition, which can be attributed to the hydrogen spillover effect 38 41 . This hydrogen spillover effect is further confirmed from the results of in situ quick XANES experiments under a H 2 atmosphere (0.6 MPa, 80 °C) (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 71%
“…Quantification of the H 2 -TPR curves (Supplementary Table 1 ) shows that the hydrogen consumed by NiO/Al 2 O 3 /Pt (1.86 mmol H 2 g –1 ) is greater than the sum of the hydrogen consumed by Al 2 O 3 /Pt (0.31 mmol H 2 g –1 ) and NiO/Al 2 O 3 (1.29 mmol H 2 g –1 ). These results demonstrate that the reduction of NiO species is promoted after Pt addition, which can be attributed to the hydrogen spillover effect 38 41 . This hydrogen spillover effect is further confirmed from the results of in situ quick XANES experiments under a H 2 atmosphere (0.6 MPa, 80 °C) (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 71%
“…57−59 It has been demonstrated that the hydrogen spillover between metal and oxide components can be precisely tuned by the intimacy between the neighboring components. 32,36 Here, a series of Co These Co 3 O 4 −ZnO catalysts are used for the CO 2 hydrogenation reaction and the effect of the intimacy between Co 3 O 4 and ZnO components on the catalytic performance is also investigated (Figures 6b and S17). During continuousflow CO 2 hydrogenation on Co 3 O 4 , a 140 min induction period can be observed where CO 2 conversion and CH 4 selectivity keep on increasing, suggesting that the catalyst state is evolving corresponding to the gradual reduction of CoO x to Co 0 (Figure S4b).…”
Section: Local Interfacial Confinementmentioning
confidence: 99%
“…Similarly, the route of hydrogen spillover has also been studied at the spatial resolution of 10 nm by the construction of sandwich nanocomposites (Figures 4C—E). [ 20 ] It demonstrated that hydrogen species could spill over at the interfaces of Pt‐TiO 2 ‐Au with high efficiency, and the maximum distance of hydrogen spillover on TiO 2 was 50 nm approximately. More importantly, we can adjust the selectivity of different reactions according to the different distances of hydrogen spillover.…”
Section: Applications Of Core‐shell Nanostructuresmentioning
confidence: 99%